The Influence of Website Quality, Perceived Ease of Use, and Consumer Trust on Purchase Decisions among Shopee Users in Kebumen Regency. - Hanwinartha Haryono; Ibnu Khafi; Agustin Riyan Pratiwi (Jurnal Bisnis dan Kewirausahaan, 2026)
The surge in e-commerce activities has heightened rivalry within digital marketplaces, forcing firms to optimize the determinants of consumer buying behavior. Even though Shopee dominates the Indonesian market, issues surrounding platform functionality, user experience, and credibility continue to critically shape online shopping choices, especially in regional areas like Kebumen Regency. Consequently, this research investigates how website quality, perceived ease of use, and consumer trust impact purchasing decisions among Shopee clients in Kebumen Regency. Utilizing a quantitative approach with a causal framework, data were gathered from 100 purposely sampled Shopee users who had completed a transaction in the preceding six months. Statistical evaluation via multiple linear regression in SPSS demonstrated that website quality, perceived ease of use, and consumer trust independently exert a positive and significant influence on buying decisions. Notably, consumer trust emerged as the primary driver, followed sequentially by perceived ease of use and website quality. Jointly, these three predictors significantly affect the dependent variable, with an R-squared value of 0.707, signifying that the model accounts for 70.7% of the variance in consumer purchase choices. These insights imply that upgrading platform quality, simplifying interface usability, and fostering user trust are pivotal tactical moves for driving sales and maintaining a competitive edge in the digital retail sector.